Hyperbaric oxygen therapy as an adjunct to corticosteroid treatment in sudden sensorineural hearing loss: a retrospective study - Skarzynski, Piotr H.; Kolodziejak, Aleksandra; Gos, Elżbieta; Skarzynska, Magdalena B.; Czajka, Natalia; Skarzynski, Henryk (Frontiers in Neurology, 2023)
Background A retrospective clinical study was conducted to test the impact of including hyperbaric oxygen therapy in the treatment of patients with sudden sensorineural hearing loss (SSNHL). Materials and methods A total of 63 adult patients with sudden sensorineural hearing loss diagnosed between 2015 and 2023 were divided into two groups: 36 patients treated with intratympanic glucocorticoid and orally administered glucocorticoid who also underwent hyperbaric oxygen therapy and 27 patients treated with intratympanic glucocorticoid and prolonged orally administered glucocorticoid (without hyperbaric oxygen therapy). An audiological evaluation was performed using pure-tone audiometry. Results Average hearing gain as measured by pure tone average was 12.5 dB HL (+/- 19.9 dB HL) in the patients treated with steroids combined with HBOT, and was 14.1 dB HL (+/- 17.9 dB) in the patients treated with steroids alone. Successful treatment (complete recovery or marked improvement) was observed in 27.8% of the patients in the first group and in 25.5% in the second group. There was no statistically significant difference between the groups. Conclusion Both groups of patients—those treated with glucocorticoids and those treated with glucocorticoids and HBOT—had similar hearing outcomes. A prospective, controlled, and randomized study would provide more reliable knowledge about the efficacy of HBOT in treating SSNHL.